Inhibition of Melanogenesis via Passive Immune Targeted Alpha-MSH Binder Polypeptide - Se-Hyo Jeong; Hun-Hwan Kim; Abigail Joy D. Rodelas-Angelia; Mark Rickard N. Angelia; Pritam Bhagwan Bhosale; Eun-Hye Kim; Tae-Sung Jung; Mee-Jung Ahn; Gon-Sup Kim (Cosmetics)
Alpha-melanocyte stimulating hormone (α-MSH) is a hormone that stimulates the formation of melanin, which is responsible for protecting the skin from UV rays. However, excessive production of melanin causes pigmentation, leading to skin disorders, such as melasma and freckles. Using phage display technology, we screened a modified hagfish VLRB (α-MSH target binding polypeptide) library for polypeptides that recognize α-MSH. This was expressed in E. coli to produce binding proteins that specifically bind to α-MSH. In this study, we investigated the effect of α-MSH binder protein on the inhibition of melanogenesis in B16F10 cells stimulated with α-MSH and the mechanism of inhibition. The α-MSH-induced inhibition of intracellular and extracellular melanogenesis was accompanied by the downregulation of TRP1 and TRP2, and melanogenesis-related proteins, such as tyrosinase and MITF, were significantly downregulated. These results suggest that the α-MSH binder polypeptide regulates melanogenesis inhibition and its associated mechanisms.